World watch geography Book 3 A geography course for grade 8 - Reilly, Carmel; Brasch, Nicholas (Karachi Oxford University Press, 2024)
It is revised according to the national curriculum of Pakistan. It integrated physical, human, and environmental geography with a special focus on Pakistan. It is for lower secondary level. It is specifically designed pathway to the GCSE examination with local and international content and builds various geographical skills and tools through maps, graphs, diagrams, photographs and statistics.
Keywords: Geography